The right to be forgotten: A new human right? - E. S. Chub (Цифровое право, 2022)
The article analyzes the need to establish the “right to be forgotten” as a new human right in the context of the correlation with the right to privacy. Its legislative development and global application call into question the relationship between private and public interests. The issue includes protection of an individual’s privacy, on the one hand, and freedom of information and expression on the other. In this context, the purpose of the study is to identify an approach to enshrine the “right to be forgotten” in a way that strikes an optimal balance of interests.Exploring the evolution of the “right to be forgotten” and the problems of its enforcement, as well as its impact on free access to information and freedom of expression, the author examines the current state of this institution. As the “right to be forgotten” originally appeared in the European Union, the article examines legislation and law enforcement practice of the “right to be forgotten” in the Russian Federation and the European Union, which leads to the conclusion that the “right to be forgotten” should be considered as an independent category in the current Russian legislation. It is proposed to supplement item 1 clause 10.3 of Federal Law “On Information, Information Technology and Information Security” with a provision that the operator of a search engine has the right to refuse to satisfy requests to remove references in cases where the information is of public interest.